Hippocampal cofilin and CFL1 gene variants are linked to alcohol use disorder phenotypes - Salamian, Ahmad; Pagano, Roberto; Skonieczna, Edyta; Kalinichenko, Liubov S.; Puchalska, Monika; Yiğit Ünlü, G.; Gajewska-Woźniak, Olga; Kruashvili, Lali; Grochowicz, Małgorzata; Wojtas, Bartosz; Gielniewski, Bartek; Harda, Zofia; et al. (Molecular psychiatry, 2025)
Alcohol use disorder (AUD) is characterized by pathological motivation to consume alcohol and cognitive inflexibility, leading to excessive alcohol seeking and use. In this study, we investigated the molecular correlates of impaired extinction of alcohol seeking during forced abstinence using a mouse model of AUD in the automated IntelliCage social system. This model distinguished AUD-prone and AUD-resistant animals based on the presence of ≥2 or <2 criteria of AUD, respectively. We used RNA sequencing to identify genes differentially expressed in the hippocampus, a brain region implicated in alcohol motivation, seeking during abstinence, and cognitive inflexibility. Our findings revealed differences in the hippocampal genes linked to the actin cytoskeleton and synaptic function, including cofilin (Cfl), and impaired synaptic transmission in the molecular layer of the hippocampal dentate gyrus (ML-DG) in ≥2 criteria mice as compared to <2 crit animals. To complement this data, we conducted local genetic manipulations in DG. Overexpression of Cfl in the polymorphic layer of the hippocampal dentate gyrus (PoDG) inhibited ML-DG synapses, increased motivation to seek alcohol and sucrose rewards, impaired extinction of seeking, and decreased reward consumption during relapse. Reducing Cfl levels had opposite effects. We also identified three SNPs in the human CFL1 gene (rs369270402, rs2376005, rs36124259) associated with increased AUD risk and found CFL1 mRNA blood levels correlated with alcohol-related hospital admissions. Overall, our study uncovers a novel mechanism linking hippocampal Cfl expression with AUD phenotypes and identifies CFL1 polymorphisms as AUD risk factor in humans.